Current Research of the Roles of IL-35 in Tumor Progression - Chongbiao HUANG; Ye TIAN; Yan CUI; Jie XU; Liang XIN; Xueling YANG; Daliang QI (Chinese Journal of Lung Cancer, 2016)
Interleukin(IL)-35 is a new member of the interleukin-12 superfamily. Since its first report in 2007, IL-35 rapidly became a research highlight in the field of immunology. Like other IL-12 superfamily members, IL-35 was a heterodimer which was composed of an α chain P35 and a β chain Epstein-Barr virus induced gene 3 (EBI3). Recent research work revealed two distinct roles of IL-35. Firstly, IL-35 is highly expressed in some kinds of inflammatory diseases and autoimmune diseases and plays import roles in the pathogenesis. Secondly, IL-35 is positively expressed in some cancers and plays some roles in the process of tumor progression. Here we demonstrate the structure and the signalling of IL-35. We reviewed the the roles of IL-35 in promoting tumor progression.